2021
DOI: 10.1101/2021.04.16.440232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling the influences of sequence and position on yeast uORF activity using massively parallel reporter systems and machine learning

Abstract: Upstream open reading frames (uORFs) are potent cis-acting regulators of mRNA translation and nonsense-mediated decay (NMD). While both AUG- and non-AUG initiated uORFs are ubiquitous in ribosome profiling studies, few uORFs have been experimentally tested. Consequently, the relative influences of sequence, structural, and positional features on uORF activity have not been determined. We quantified thousands of yeast uORFs using massively parallel reporter assays in wildtype and ∆upf1 yeast. While nearly all A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 90 publications
2
31
0
Order By: Relevance
“…It was reported that among the 407 mRNAs containing a single functional AUG-uORF wherein mutating the uORF significantly altered reporter expression by > 1.5-fold, all but 13 of the uORFs functioned to inhibit reporter expression. Among the 144 mRNAs containing a single functional NCC-uORF, only 13 of the uORFs influenced reporter expression either positively or negatively by > 1.5-fold, reflecting the weaker effects of NCC-versus AUG-initiated uORFs on downstream translation (May et al 2023). Our analysis of the 394 mRNAs containing a single inhibitory AUG-uORF—the only group large enough for statistical analysis of TE changes—revealed little or no change in median TE in response to SM treatment or to the eIF2AΔ mutation in the presence or absence of SM (Figure 6A(iii), cols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that among the 407 mRNAs containing a single functional AUG-uORF wherein mutating the uORF significantly altered reporter expression by > 1.5-fold, all but 13 of the uORFs functioned to inhibit reporter expression. Among the 144 mRNAs containing a single functional NCC-uORF, only 13 of the uORFs influenced reporter expression either positively or negatively by > 1.5-fold, reflecting the weaker effects of NCC-versus AUG-initiated uORFs on downstream translation (May et al 2023). Our analysis of the 394 mRNAs containing a single inhibitory AUG-uORF—the only group large enough for statistical analysis of TE changes—revealed little or no change in median TE in response to SM treatment or to the eIF2AΔ mutation in the presence or absence of SM (Figure 6A(iii), cols.…”
Section: Resultsmentioning
confidence: 99%
“…uORFs with mean RPF counts below two or mean CDS RPF counts below 32 in the combined samples (two replicates each) were excluded from the analysis. The compilations of annotated translated uORFs (Martin-Marcos et al 2017), evolutionarily conserved translated uORFs (Spealman et al 2018), or functional uORFs whose elimination by start codon mutation conferred a consistent and statistically significant alteration in translation of the downstream GFP CDSs in reporter constructs (May et al 2023), were all published previously and are provided in Figure 6-source data 5-7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reached different conclusions concerning the impact of IF uAUGs on translation [15,20,27,28]. To clarify this, we determined the relationship between the location of OOF and IF uAUGs in the 5'UTR and the translation output of the mRNAs, in both yeast and human sequences, synthetic or endogenous.…”
Section: Reporter Sequences Differ In Translation-relevant Properties...mentioning
confidence: 96%
“…These assays have improved our understanding of translation control and mRNA stabil ity. Previous works have characterized Kozak strength, 23 uORFs, [24][25][26] IRESs, 27,28 codon optimality, 29,30 RNA struc ture, 31 microRNA binding sites, 32 and the effects of vari ation in human UTRs. [33][34][35][36] These assays have also iden tified novel sequence motifs driving translation and de cay.…”
mentioning
confidence: 99%